Antibiosis associated to Lactobacillus acidophilus growth .1. Strain selection and study of an alternative medium using whey - Pinto, Marcos Franke [UNESP]; Ponsano, EHG; CastroGomez, RJH (Inst Tecnologia Parana, 1996)
The production of antimicrobial compounds of some strains of Lactobacillus acidophilus has been studied. They have been grown in whey supplemented with soy milk. It has been found that the production of compounds is able to inhibit the growing of both target bacteria analysed: Staphylococcus aureus and Escherichia coli. The results showed a significant variation (p>0.05) depending on the strain of L. acidophilus and on the level of supplementation utilized. Most of the inhibition observed resulted from the presence of the lactic acid produced. It has also been found the production of other antimicrobial compounds showing inhibitory capacity. The action of these compounds was influenced by the substract pH.
Keywords: Lactobacillus acidophilus; antibiosis; whey; fermentation